Psychotropic Medications-Induced Tardive Dyskinesia and Associated Factors Among Patients with Mental Illness in Ethiopia - Kumsa A; Girma S; Alemu B; Agenagnew L (Dove Medical Press, 2020)
Assefa Kumsa, Shimelis Girma, Bezaye Alemu, Liyew Agenagnew Department of Psychiatry, Faculty of Medical Science, Institute of Health, Jimma University, Jimma, EthiopiaCorrespondence: Liyew AgenagnewJimma University, 378, Jimma, EthiopiaTel +251 912806976Email liyew2003@gmail.comBackground: Tardive dyskinesia (TD) remains a significant burden especially among patients taking psychotropic medications, and it is associated with adverse effects that can lead to subjective suffering, stigma, poor compliance to medication, and poor quality of life. However, it is unrecognized and overlooked in clinical settings. So, this study aimed to assess the magnitude of tardive dyskinesia and associated factors among mentally ill patients attending follow-up treatment at Jimma University Medical Center Psychiatry clinic, Jimma, Southwest Ethiopia, 2019.Methods: Institutional-based cross-sectional study design was conducted in 417 samples. Participants were selected by systematic random sampling techniques. Data were collected by a semi-structured interviewer-administered questionnaire, and the document was reviewed to obtain the patient’s profile. Tardive dyskinesia was assessed by using the Extrapyramidal Symptom Rating Scale after informed consent was obtained from respondents. Data entry was done by EpiData version 3.1, and analysis was done by using SPSS 22.0 statistical software. Binary logistic regression and multivariate logistic regression were used to see the association and to identify independent factors at a p-value of < 0.05.Results: Prevalence of drug-induced tardive dyskinesia was 15.4% (CI 95%: 12.0, 19.3). Female, age range between 30 and 44 years, having a diagnosis of major depressive disorder with the psychotic feature, taking chlorpromazine equivalent dose ˃600mg, and taking anticholinergic medications were variables positively associated with tardive dyskinesia, whereas cigarette smoking was negatively associated with tardive dyskinesia.Conclusion: The prevalence of drug-induced tardive dyskinesia in this study was high. Prescribing medications less than 600mg equivalent dose of chlorpromazine, giving attention for female patients, patients having a diagnosis of major depressive disorder, and reducing giving anticholinergic medications will be important measures for clinicians to reduce the occurrence of tardive dyskinesia.Keywords: mental illness, antipsychotics, tardive dyskinesia, Jimma